Aplicación de la ecuacion de Schrodinger en heteroestructuras semiconductoras de baja dimensionalidad - Francis Armando Segovia (Tecnura, 2013)
The research presented in the following paper concerns condensed matter areas in the field of semiconductor physics. This research uses the basic principles of quantum mechanics, particularly effective mass approximation. The aim of this paper is to determine the energies of ground state as well as the energies of electron-hole transition when a semiconductor heterostructure GaAs-Ga1-xAlxAs is immersed in a barrier of Ga1-yAlyAs, by applying hydrostatic pressure. The methodology proposed in the present work analytically solves Schrödinger’s second-order differential equation to find solutions and allow determining the corresponding differential equation together with the energies of transition in the ground state. This is accomplished through the application of hydrostatic pressure. The main results were obtained using software package Mathematica 5.0. Results indicate a regime of strong confinement for small widths of the potential well in semiconductor heterostructures, where the confinement potential lessens with pressure for the charge-carrier function (electron-hole). However, the findings demonstrate that, in the regime of weak confinement, the effects of hydrostatic pressure on the heights of the barrier are more significant, and there is also a reduction in carrier energies.